A comparative study on the role of oral mifepristone and endocervical prostaglandin as preinduction cervical ripening agent - Mohapatra, Sanghamitra; ., Samarpita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Induction of labour is one of the most common interventions practised in modern obstetrics with up to 20% of pregnant women having labour induced in some countries. Induction rates have been influenced by several reports worldwide, which claimed that an active induction policy, led to substantial reduction in perinatal and maternal morbidity and mortality. A ripe or favourable cervix is a pre-requisite for successful vaginal birth. This study is conducted with an aim to compare the efficacy of mifepristone and dinoprostone as a cervical ripening and priming agent for induction of labour and their safety and fetomaternal outcome. Methods: It was a prospective comparative study in the Department of Obstetrics and Gynecology, M.K.C.G. Medical college, Berhampur from October 2017 to October 2019. 100 cases with bishop score less than 6 were subjected for pre induction ripening. These cases were assigned at random either to study group, who were given single dose oral mifepristone 200 mg and control group with single dose intracervical E2 gel. All the cases were examined to check the bishop score. In cases of control cases, second dose was given after 6 hours, if there was no improvement in bishop score. At the end of 24 hour if bishop score <6, it was called as failed induction. Results: 90% of mifepristone gr and 56% of dinoprostone gr had improved Bishop score>6 after 6hr.32 cases required oxytocin augmentation in mifepristone gr where as it was 57 in dinoprostone. Drug administration to delivery interval was 19.40 hour in mifepristone gr and 15 hour in dinoprostone gr. More vaginal delivery and less fetal distress in mifepristone gr. Conclusions: Mifepristone is an effective agent for cervical ripening with better fetomaternal outcome compaired to dinoprostone.